182k views
4 votes
If f(x)=2x^2-x-6 and g(x)=x^2-4 find f(x)/g(x)

User Thermans
by
5.5k points

2 Answers

5 votes

Answer:

See image below

Explanation:

If f(x)=2x^2-x-6 and g(x)=x^2-4 find f(x)/g(x)-example-1
User MiscellaneousUser
by
6.5k points
2 votes

Answer:


\boxed{\boxed{(f(x))/(g(x))=(2x+3)/(x+2)}}

Explanation:

Here,


f(x)=2x^2-x-6


=2x^2-4x+3x-6


=2x(x-2)+3(x-2)


=(2x+3)(x-2)

And


g(x)=x^2-4


=x^2-2^2


=(x+2)(x-2)

Therefore,


(f(x))/(g(x))=((2x+3)(x-2))/((x+2)(x-2))


=(2x+3)/(x+2)

User Furman
by
5.9k points